2018
DOI: 10.18506/anemon.400497
|View full text |Cite
|
Sign up to set email alerts
|

Teknoloji Entegrasyonuna Yönelik Öz-Yeterlik Algısı Ölçeğinin Türkçeye Uyarlanması

Abstract: Bu araştırmanın amacı, Wang, Ertmer ve Newby (2004) tarafından geliştirilen Teknoloji Entegrasyonuna Yönelik Öz-Yeterlik Algısı Ölçeği'ni Türkçe'ye uyarlamaktır. Ölçeğin geçerlik ve güvenirlik analizlerini yapmak için Afyon Kocatepe Üniversitesi Eğitim Fakültesi'nde öğrenim gören 748 öğretmen adayından veri toplanmıştır. Ölçeğin yapı geçerliği için açımlayıcı ve doğrulayıcı faktör analizleri gerçekleştirilmiş ve benzer yapı elde edilmiştir. Ölçeğin güvenirlik analizinde Cronbach Alfa İç Tutarlık katsayısı hesa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 10 publications
1
6
0
1
Order By: Relevance
“…In the analysis made according to the gender variable, a significant difference was found in favour of male students. This result is parallel to the findings of previous studies (Tekiṅarslan, 2008;Pamuk & Peker, 2009;Ünal & Teker, 2018). A significant difference was found in the perception of self-efficacy of faculty of education students in using computer technologies according to the department.…”
Section: Findings Discussion and Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…In the analysis made according to the gender variable, a significant difference was found in favour of male students. This result is parallel to the findings of previous studies (Tekiṅarslan, 2008;Pamuk & Peker, 2009;Ünal & Teker, 2018). A significant difference was found in the perception of self-efficacy of faculty of education students in using computer technologies according to the department.…”
Section: Findings Discussion and Resultssupporting
confidence: 89%
“…This result is parallel to the findings of previous studies. The study conducted by Ünal and Teker (2018), observed that the self-efficacy perceptions of the students of education faculty towards technology integration were high. It was found that the digital competence levels of the education faculty students were at a medium level.…”
Section: Findings Discussion and Resultsmentioning
confidence: 99%
“…In this study, two data collection tools were used. Technology Integration Self-efficacy Scale (TISS) which was developed by Wang, Ertmer and Newby (2004) and translated into Turkish by Ünal and Teker (2018). TISS included 19 items within 2 sub-dimensions as use of information technologies and making students use of information technologies.…”
Section: Methodsmentioning
confidence: 99%
“…) tarafından geliştirilen veÜnal ve Teker (2018) tarafından Türkçe'ye uyarlanan, Teknoloji Entegrasyonuna Yönelik Öz-yeterlik Algısı (TEYÖ) ölçeği ön test ve son test olarak uygulanmıştır. Bu ölçek 19 maddeden ve iki alt boyuttan oluşmaktadır.…”
unclassified
“…Following two calculations in pre and post-test measures, the findings were 0.94 and 0.96 (Wang et al, 2004). In the Turkish adaptation study, Cronbach alphas for CTCS, EICTU, and the whole scale were 0.91, 0.87., and 0.94, respectively (Ünal & Teker, 2018).…”
Section: Data Collecting Toolsmentioning
confidence: 98%